Post Conditionally Unconstitutional of Job Creation Law: Quo Vadis Legal Certainty? - A'an Efendi; Fradhana Putra Disantara (Yuridika, 2022)
Enigma emerged when the Constitutional Court declared that Law Number 11 of 2020 concerning Job Creation (UU CK) unconstitutional. The purpose of this legal research is to review the legal dynamics of the UU CK after the Constitutional Court Decision No. 91/PUU-XVIII/2020 based on the point of view of the formal review and procedural justice, as well as reviewing the relevance of the Decision as a monumental decision; while at the same time analyzing the phenomenon of 'conditionally unconstitutional' in the perspective of legal certainty and expediency. This legal research uses a conceptual approach and a statutory approach. The legal materials of this legal research consist of primary legal materials, secondary legal materials, and non-legal materials. The study results stated that the Constitutional Court Decision No. 91/PUU-XVIII/2020 is not a monumental decision, considering an omission of "freeze" norms from the UU CK. Meanwhile, if it is studied based on procedural justice and the conception of a formal review, then the UU CK should be null and void by law. Then, 'Constitutional Conditional' in the Decision of the Constitutional Court No. 91/PUU-XVIII/2020 provides legal chaos. There is a contradiction that the UU CK is declared not legally binding as a consequence of 'formal defects' from the process of forming the UU CK. Thus, the suggestion from the researcher is that the government can ratify a standard rule in the law regarding the formation of legislation regarding the construction of an omnibus law scheme.